2019
DOI: 10.4025/actascibiolsci.v41i1.35655
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of polysulfated fractions from the green seaweed <i>Caulerpa cupressoides</i> and actions on thrombin generation <i>in vitro

Abstract: Caulerpa cupressoides produces sulfated polysaccharides (Cc-SPs) with serpin-dependent anticoagulant effect, but their actions on thrombin generation (TG) are unknown. This study aimed to partially characterize Cc-SPs and examine their potential as modulators of TG. Infrared analysis characterized extract containing three ulvan fractions (Cc-SP1, -SP2 and -SP3) separated by DEAEcellulose chromatography, with differences in the relative proportions of sulfate (10.99-18.38%) and total sugars (46.59-51.12%), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This result appeared on gel electrophoresis, after the use of Stains-all alone, in brown color, suggesting uronic acid-containing glycans in A. muscoides and purity of the agarocolloid confirmed by its structure as identified on FT-IR and NMR analyses (Quinderé et al, 2014;Vanderlei et al, 2016;Rodrigues et al, 2021) and by comparisons with other authors who found agar polysaccharide in Acanthophora (Duarte et al, 2004) and other seaweed species (Ferreira et al, 2012;Recalde et al, 2016). Similar to our study, polysaccharides isolated from animal (Volpi & Maccari, 2002;Andrade et al, 2017), plant (Souza et al, 2015) and seaweed (Rodrigues et al, 2017b and2019) were also characterized by their specific colors, reinforcing the use of Stains-all alone as a more precise strategy to also reveal acidic polysaccharides in red seaweeds than in combination with toluidine blue (Rodrigues et al, 2021). Additionally, HMBC analysis showed a doublet signal due to nondecoupling of the pulse sequence relatives to a sulfated galactan pyruvate form of six-membered cyclic ketal, including O-4 and O-6 positions (4,6-O-(1'carboxy)-ethylidene cyclic ketals), since that this structural feature has not been frequently found in agarophytes (Cardozo et al, 2007;Ferreira et al, 2012;Mourão, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This result appeared on gel electrophoresis, after the use of Stains-all alone, in brown color, suggesting uronic acid-containing glycans in A. muscoides and purity of the agarocolloid confirmed by its structure as identified on FT-IR and NMR analyses (Quinderé et al, 2014;Vanderlei et al, 2016;Rodrigues et al, 2021) and by comparisons with other authors who found agar polysaccharide in Acanthophora (Duarte et al, 2004) and other seaweed species (Ferreira et al, 2012;Recalde et al, 2016). Similar to our study, polysaccharides isolated from animal (Volpi & Maccari, 2002;Andrade et al, 2017), plant (Souza et al, 2015) and seaweed (Rodrigues et al, 2017b and2019) were also characterized by their specific colors, reinforcing the use of Stains-all alone as a more precise strategy to also reveal acidic polysaccharides in red seaweeds than in combination with toluidine blue (Rodrigues et al, 2021). Additionally, HMBC analysis showed a doublet signal due to nondecoupling of the pulse sequence relatives to a sulfated galactan pyruvate form of six-membered cyclic ketal, including O-4 and O-6 positions (4,6-O-(1'carboxy)-ethylidene cyclic ketals), since that this structural feature has not been frequently found in agarophytes (Cardozo et al, 2007;Ferreira et al, 2012;Mourão, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Technology, v. 43, e55043, 2021 Cephalin or thromboplastin-devoid TG allowed to examine whether SP-Am would stimulate 60-fold diluted plasma, and suggested that, in the concentration range tested, the modestly TG-induced algal polysaccharide as FXII-speculated procoagulant effect previously related to low molecular mass accordingly, while UHEP did no activate FXII (Quinderé et al, 2014). This was also postulated for a SPs fraction from the green seaweed Caulerpa cupressoides, but 100% TG inducing at highest dose (Rodrigues et al, 2019). Mansour et al (2017) revealed that the oversulfated fucosylated chondroitin sulfate from the sea cucumber Holothuria polii body wall exhibited unusual procoagulant effect by means of calibrated automated thrombography.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations